Distribution of total suspended solids and dynamics of the estuarine turbidity maximum in the Ipojuca River estuary (Ocean and Coastal Research, 2024)
This study focused on the distribution of total suspended solids (TSS) concentration along the Ipojuca Riverestuary and on identifying the average location of the estuarine turbidity maximum (ETM) zone consideringthe seasonality of its rainfall and tidal regime. This research was carried out along a 13.6 km stretch of thechosen river, with 21 sampling stations during the rainy (Jun-Jul/17) and dry periods (Dec/17). Temperature andsalinity data were obtained at each station using CTD profiling. Furthermore, current intensity and direction weremeasured using a current meter, and water samples were collected to determine TSS concentrations. The watercolumn showed vertically homogeneous temperature (~27° C). Salinity distribution varied seasonally and alongthe tidal cycle throughout the system. The estuary shows a weakly to moderately stratified water column thatintensifies itself upstream. At just 2.28 km from the river mouth (second station), salinity varies by 0.2-32.9. Thisstratification primarily stems from the constriction of its river mouth, trapping freshwater in its interior. Currentsshowed higher values during the rainy period (-5 to 95.8 cms-1). TSS concentrations were higher during the rainyseason, ranging from 8.6 to 241.2 mg L-1 during spring tides and from 6.5 to 223.0 mg L-1 during neap tides.The ETM was located at 1.8-2.2 km from the river mouth during the rainy season and at 2-8 km during the dryseason. The ETM coincided with the boundaries of salt propagation in the estuary, corresponding to salinitiesof 0.2-10, and longitudinal currents ranging from 60 to -10 cm s-1, indicating the mixing zone of water masses.Since the ETM is also associated with the area of highest sediment deposition in the estuary, it is likely that mostmaterials transported to the estuary that are associated with sediment transport remain trapped in this zone,making it an important area for further studies.